Genomic analysis of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) causing infections in children—a Spanish multicenter study - García-Cobos, Silvia; Seco Alberca, Natalia; Bravo-Queipo-de-Llano, Blanca; Casquero-García, Verónica; Ramírez de Arellano, Eva; Calvo, Cristina; Ruíz-Carrascoso, Guillermo; Falces-Romero, Iker; Larrosa Escartín, Nieves; Viñado-Perez, Belén; Martínez-López, Miguel Ángel; Melendo Pérez, Susana; et al. (Frontiers in Microbiology, 2025)
ObjectivesStaphylococcus aureus is one of the most common human pathogens causing skin and soft tissue infections (SSTIs) among children. This study investigated the molecular traits of community-associated methicillin-resistant S. aureus (CA-MRSA) isolates causing infections in children in Spain.MethodsAntibiotic susceptibility testing and whole-genome sequencing were performed in 98 CA-MRSA isolates (4.2 median age, 52% males). The phylogenetic relationship, antibiotic resistance, virulence, and plasmid replicon genes content were investigated.ResultsResistance rates were found as follows: Erythromycin, 42.9%, which could be explained due to the presence of erm(C), mph(C), and msr(A) genes; tobramycin, 27.5%, which could be explained due to the presence of aac(6′)-Ie/aph(2″)-Ia and aadD1 genes; tetracycline, 25.5%, which could be explained mainly due to the presence of tet(K) genes; levofloxacin and moxifloxacin, 19.4%, which could be explained primarily due to the mutations in gyrA and parC genes; and gentamicin, 15.3%, which could be explained due to the presence of aac(6′)-Ie/aph(2″)-Ia gene. The most prevalent lineage was ST8-IVc and t008. Most isolates were genetically diverse, except for three groups of isolates from the same hospital and one group of isolates from different hospitals. These had less than or equal to 5 allele differences by core-genome multilocus sequence typing (cgMLST) analysis or 0–6 core single-nucleotide polymorphisms (SNPs) by core-genome SNP-based analysis. Phage-encoded Panton–Valentine leukocidin (PVL) genes were found in 75.5% of the isolates. Other common virulence genes were related to adhesion (capA and capP), lipid degradation (geh), hemolysis (hlb, hld, hlgABC, and hly/hla), and tissue destruction (sspAB).ConclusionThis study observed a high genetic diversity among CA-MRSA isolates causing community-acquired infections in children in Spain, with ST8-IVc as the most prevalent lineage. Nevertheless, genetic relatedness of some isolates from the same as well as different hospitals suggests the dissemination of CA-MRSA among children by contact.